O ensino jurídico no Brasil e o estado democrático de direito: análise crítica do ensino do direito penal - Toledo, Cláudia Mansani Queda de (2008)
The Masters dissertation under the title The Legal Education in Brazil and the democratic rule of law - critical analysis of teaching criminal law, is an analysis of the disparity observed between the teaching of criminal law and social reality as it is part and indicates the need for a new look to the teaching of criminal law, consistent with the expectations of modern society. The work shows a crisis in legal education, disclosed the meeting between what is taking place within the faculties of law and that perpetrators of Education considered modern feel as ideal way to a training committed to social dialectics. To locate the subject, presents a historical review of the Brazilian legal education in order to verify the remote reflected in the current model adopted and point to existing legislation that regulates. The objectives are at identifying what the expected profile for graduates of colleges of law and whether or not they are being considered qualified to confront this new moment of the social teaching of criminal law in the face of the guiding principles of democratic rule of law. Another goal is to uncover what role the university in the democratic rule of law as an appropriate forum to bring the work practices of a pipeline and processing dialectically adjusted to the clamor of social reality. The study also puts the science of law and guided always by an ideology and shows the importance of attending the university education together with research and extension, a prospect inseparable